2018
DOI: 10.1002/hbm.24404
|View full text |Cite
|
Sign up to set email alerts
|

Automatic localization of the subthalamic nucleus on patient‐specific clinical MRI by incorporating 7 T MRI and machine learning: Application in deep brain stimulation

Abstract: Deep brain stimulation (DBS) of the subthalamic nucleus (STN) has shown clinical potential for relieving the motor symptoms of advanced Parkinson’s disease. While accurate localization of the STN is critical for consistent across-patients effective DBS, clear visualization of the STN under standard clinical MR protocols is still challenging. Therefore, intraoperative microelectrode recordings (MER) are incorporated to accurately localize the STN. However, MER require significant neurosurgical expertise and len… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
59
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(61 citation statements)
references
References 99 publications
(186 reference statements)
0
59
2
Order By: Relevance
“…subthalamic nucleus (STN) or GPi) is directly correlated with the success of the DBS procedure and reduction of adverse effects (Ellis et al, 2008;Marks et al, 2009;Paek et al, 2013;Patel et al, 2015;Richardson et al, 2009;Rolston et al, 2016;Welter et al, 2014). Correct anatomical target identification is characterized not only by the target's center of mass, but also by its boundaries (Kim et al, 2019). Thus, precise identification of both GPe and GPi and their lamina boundary is of great importance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…subthalamic nucleus (STN) or GPi) is directly correlated with the success of the DBS procedure and reduction of adverse effects (Ellis et al, 2008;Marks et al, 2009;Paek et al, 2013;Patel et al, 2015;Richardson et al, 2009;Rolston et al, 2016;Welter et al, 2014). Correct anatomical target identification is characterized not only by the target's center of mass, but also by its boundaries (Kim et al, 2019). Thus, precise identification of both GPe and GPi and their lamina boundary is of great importance.…”
Section: Introductionmentioning
confidence: 99%
“…Although atlases, which are typically defined in a normalized space, have shown great importance in retrospective population studies Horn, Neumann, et al, 2017;Horn, Reich, et al, 2017;Kim et al, 2019), several recent studies have shown that variablity exists of the size and shape of deep brain structures between different subjects (Abosch et al, 2010;Duchin et al, 2018;Lenglet et al, 2012;Patriat et al, 2018). This inherent inter-patient variability is not fully captured by atlas-based segmentations, as they provide a single, averaged shape of brain structures, be it deterministic or probabilistic.…”
Section: Introductionmentioning
confidence: 99%
“…Automatic identification and segmentation of medical imageries benefit the planning and guidance of modern surgery [1][2][3][4][5], clinical investigations [6][7][8][9][10], rehabilitation [11][12][13], and so forth. High-quality reconstructive anatomical morphology provides convenience on surgery planning and the understanding between organ functionalities and pathological diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Among those developed techniques, state-of-the-art methodologies on the field of magnetic resonance image (MRI) processing successfully combined several merits from interdisciplinary methods [16][17][18] and exhibit an opportunity to track brain regions related to relevant diseases [19,20]. For instance, precise identification and segmentation of subthalamic nucleus from three-dimensional medical imageries facilitate the automatic planning of deep brain stimulation, and the clinical result has also shown clinical potential for relieving the motor symptoms of advanced Parkinson's disease [8,21,22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation